A Framework from Peer-to-Peer Electricity Trading Based on Communities Transactions - Moreno, Ricardo; Hoyos, Cristian; Cantillo, Sergio (International Journal of Energy Economics and Policy, 2021)
Recently, several authors and reports inform about peer-to-peer transactions of goods and services. Usually, the electricity markets work trading energy at large scale in wholesale electricity markets. Given the integration of distributed energy resources such as PV generators, storage at small scale, demand response and electric vehicles then there are new options to trade energy at small scale by focusing in the producer-consumer relationship. This derives in alternatives based on peer-to-peer (P2P) electricity markets to trade energy employing tools as the blockchain and deployment of distributed energy resources (DERs). This paper presents a framework to trade energy at small scale with a flexible hybrid model of P2P based on transactions between communities and peers, for each period of time, each peer can change its role, the prosumer and producer peers can offer their generated energy. The consumer peers can adjust their consumption behavior based on price and quantity. Thus, the role of the community manager comes into play to associations between peers as an intermediary of the community and the grid. Therefore, a model of transactions with P2P offers was developed for different structures and sales prices. Finally, the framework to trade energy in a hybrid P2P model is evaluated in a demand curve considering a 24-hour period for several cases. Keywords: Blockchain, Distributed Energy Resources, Electricity Markets, Microgrids, Peer-to-peer. JEL Classifications: O12, Q21, Q42, Q47